1996
DOI: 10.1007/bf00124501
|View full text |Cite
|
Sign up to set email alerts
|

Towards an understanding of the molecular basis of hydrophobicity

Abstract: The modern view is stressed that the structuring of water around nonpolar solutes, a process called hydrophobic hydration, actually favors the solubility of nonpolar solutes in water, its associated positive free energy of transfer arising from the enthalpic input required to create a cavity in water to accommodate the solute. The results of a series of molecular dynamics simulations of methane in SPC/E water at different temperatures are reported. These results show the existence of a larger fraction of broke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…An alternative approach does not regard the structuring of the water molecules as the main reason for hydrophobic interactions. Instead, it involves a positive enthalpy resulting from the rupture of several hydrogen bonds in order to create a cavity in the water structure that subsequently accommodates the nonpolar compound 306, 307. In agreement with this hypothesis, calorimetric measurements found that contributions of 25–100 % of the protein–ligand binding enthalpy originate from solvent reorganization 308…”
Section: Binding Affinity As a Results Of Inter‐ And Intramolecularmentioning
confidence: 74%
“…An alternative approach does not regard the structuring of the water molecules as the main reason for hydrophobic interactions. Instead, it involves a positive enthalpy resulting from the rupture of several hydrogen bonds in order to create a cavity in the water structure that subsequently accommodates the nonpolar compound 306, 307. In agreement with this hypothesis, calorimetric measurements found that contributions of 25–100 % of the protein–ligand binding enthalpy originate from solvent reorganization 308…”
Section: Binding Affinity As a Results Of Inter‐ And Intramolecularmentioning
confidence: 74%
“…Several years ago, Muller proposed his modified hydration-shell hydrogen-bond model to calculate the contributions to the thermodynamics of hydration from the formation of hydrogen bonds between water molecules in the hydration shell of nonpolar substances. , His simple model predicted that hydration-shell hydrogen bonds would have higher bond-breaking enthalpies and entropies than those in pure water and that it manifested itself by the existence of a larger fraction of broken hydrogen bonds in the hydration shell than in the bulk. , Such predictions about the fraction of broken hydrogen bonds were later confirmed by computer simulations. …”
Section: Introductionmentioning
confidence: 99%
“…16,8 Such predictions about the fraction of broken hydrogen bonds were later confirmed by computer simulations. [17][18][19] A series of simulations of solutions of methane in both pure and salt (NaCl) water have been reported recently, showing for the first time the existence of an enhanced hydrophobicity in the presence of salt. 20,21 In this paper we report the results of using Muller's modified hydration-shell hydrogen-bond model to compute and contrast the hydrogen-bond contributions to hydrophobic hydration in pure and saltwater.…”
Section: Introductionmentioning
confidence: 99%
“…Allerdings ist diese klassische Sichtweise nicht allgemein akzeptiert 298, 302. Ein alternativer Ansatz sieht nicht in der Strukturierung der Wassermoleküle die Ursache für hydrophobe Wechselwirkungen, sondern in einer positiven Enthalpie bedingt durch das Aufbrechen von H‐Brücken zur Bildung einer Kavität im Wasser, die anschließend die unpolare Substanz aufnimmt 306, 307. Dementsprechend wurden in kalorimetrischen Studien Beiträge von 25 bis 100 % der Bindungsenthalpie von Liganden an Proteine bedingt durch Lösungsmittelreorganisation bestimmt 308…”
Section: Bindungsaffinität Als Resultat Inter‐ Und Intramolekulareunclassified